O-315 A war in Europe?: Ukrainian scientists' struggle for life and future, relocation and securing of frozen biomaterials. (30th June 2022) - Aydin, B; Dorofeyeva, U; Strelko, G; Ulanova, V; Hudkova, D; Maliuta, O; Pischana, T; Korobko, M; Lyzohub, O; Kotliarova, E; Simiian, P; Kozyra, O; et al.
Abstract: We should describe war as an attack maneuver by two countries or organizations against each other in line with their mutual interests when giving it significance. What is going on in Ukraine is more than a war; it is people's effort to defend their future, past from this genocide attacks which done by Russian Federation. Russian Federation's attacks not only damage all healthcare and scientific institutions but also make any future advancement in healthcare impossible. Millions of Ukrainians and foreigners residing, working, and living in the country were uprooted and forced to flee. While the strikes rendered general healthcare and fertility services inoperable, they also made protecting and maintaining all stored gametes and embryos challenging. Many infertility patients and thousands of IVF couples who have undergone oncofertility cryopreservation have been put at risk due to these attacks. While what happened in Ukraine affects thousands of infertility patients worldwide, the horrific situations faced by hundreds of IVF specialists, embryologists, nurses, and other allied healthcare workers, along with the losses they have suffered and the uncertainty of their future, reveal that the situation is far more than a war and that it is a genocide situation that no one who values life should accept. Embryologists were trying to freeze embryos and gametes at different developmental stages of dozens of patients in their incubators on February 24, when the Russian Federation's attacks started, ignoring the vital risks, again, on the day of the war beginning, and IVF specialists who performed egg collection and embryo transfer procedures for all patients who were in that day before, as well as all the other healthcare workers who took part in this process — they all showed how professionally and willingly the IVF service in Ukraine is provided. When the attacks became more intense in the days ahead, hundreds of Ukrainian embryologists risked their lives and the lives of their families to transport frozen samples to secure regions within the country and even beyond, sending a powerful message to the entire world. Expert embryologists moved all frozen components to secure locations, adhering to all safety regulations and regularly monitoring temperature and liquid nitrogen levels. It is impossible to say that this transportation method is not at risk from attacks. The transfer process was carried out fully to protect patients, with individual decisions made without acquiring patient consent forms or essential approvals due to the urgency of the decisions made from the moment the attacks had begun. The samples obtained abroad, on the other hand, were transported to European countries after all of the necessary legal registrations and procedures were completed at customs, following long and exhausting land journeys. Storage tanks that can be transferred within Ukraine were moved to western cities and secured in clinics with medical licenses. Samples were also secured in clinics with medical licenses outside of Ukraine, and all essential legal documents and regulations were completed. While over 70, 000 frozen embryos have been carried abroad, over 10, 000 frozen eggs have been transported for egg banking. Thousands of testicular tissue samples and hundreds of ovarian tissue samples were also transported. In Ukraine, thousands of frozen embryo and sperm samples are now successfully preserved. So far, no embryo harm or difficulties with liquid nitrogen delivery have been recorded. However, if Russian Federation's attacks continue, the difficulties will inevitably worsen, putting hundreds of frozen patient samples in danger. Hundreds of embryologists, IVF specialists, nurses, and paramedics were also laid off, and many were forced to flee the country. The Russian Federation's attacks on the Ukrainian people have put human lives and the future prospects of countless infertility patients in jeopardy.